External Bremsstrahlung Studies on Films of Lead Monoxide Filled Polycarbonate Composite - V. A. Kandagal; B. Lobo (National Research and Innovation Agency, 2023)
The development of high-Z (high atomic number) radiation shielding materials is vital in order to protect personnel who work with harmful gamma radiation sources. At the same time, the emission of external bremsstrahlung (EB) radiation in those shielding materials when the radiation source emits beta particles as well as gamma radiation is also of prime concern.The production of EB in films of lead monoxide (PbO) loaded polycarbonate (PC) composite at eleven different filler levels (FLs) varying, in terms of weight fraction, from 0.0Â % up to 10.0Â % were investigated experimentally by using beta particles from strontium-90/yttrium-90 (90Sr/90Y) radioactive source. A nonlinear relation is observed between EB intensity and target thickness. The effective atomic numbers of the prepared PbO-filled PC composite films (at different FLs) were determined via EB measurements, followed by calculations, and the values obtained were compared with the modified atomic numbers which were determined for the same composite films (at different FLs) using the Markowicz and VanÂ Grieken equation, and it was found that they are in good agreement. Finally, the atomic number dependence of EB in these composite films (PbO-filled PC composites) has been studied. It is obtained that the intensity of EB spectra depends on the square of the atomic number of the target material.